Method for preparing metal oxide nano powder through molten salt quenching method
The preparation of metal oxide nanopowder by molten salt quenching solves the problems of high energy consumption, high cost and complex process in the prior art, and realizes the controllability of the morphology and size of the nanopowder, which is suitable for the preparation of a variety of functional materials.
Patent Information
- Application Number
- CN202510101398.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing preparation methods for metal oxide nanopowders have problems such as high energy consumption, high production costs, cumbersome steps, and difficulty in controlling the morphology and size, which limits its industrial application in the fields of catalysis, energy storage, etc.
Metal oxide nanopowders are prepared by molten salt quenching method. By adjusting the ratio of precursor salt and metal source salt, the ratio of quenching liquid, the reaction temperature and time, the controllability of the morphology, size and type of the nanopowder is achieved.
It realizes the rapid and efficient preparation of various metal oxide nanopowders, reduces energy consumption and production costs, simplifies process steps, improves the versatility and performance of materials, and is suitable for electrodes, catalysts and other fields.
Smart Images

Figure CN119911960A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder material preparation, and in particular relates to a method for preparing metal oxide nano powder by a molten salt quenching method. Background Art
[0002] There are many types of metal oxides with wide applications. Different metal oxides have their own advantages in redox activity, valence state changes, environmental friendliness, stability, etc., and have great potential and prospects in catalysis, energy storage, sensing and other fields. The nanopowder form of metal oxides has excellent properties different from bulk large-size materials and has been widely explored by researchers. Especially in the field of energy storage, nanopowders can adapt to various forms of current collectors to construct rigid or flexible energy storage devices. Compared with nanofilms, nanopowders can more flexibly control the loading amount to meet industry needs. In the field of catalysis or sensing, nanopowders can be better distributed in the target, so that the reaction sites can be more exposed, effectively improving the functional effect.
[0003] At present, the preparation of metal oxide nanopowders includes solvothermal method, chemical precipitation method, etc. For example, patent CN201710216261.0 discloses a method for preparing transition metal oxide electrode materials with various morphologies. This method prepares transition metal oxides by solvothermal method under the action of precipitant and surfactant, uses alcohol or water as solvent, produces more waste liquid, and the synthesis process requires high temperature and high pressure, with high energy consumption, high production cost, and difficult control, which is not conducive to large-scale production. Therefore, although the solvothermal method can obtain a variety of special morphologies of metal oxides, the preparation conditions are complex and harsh, and the morphology and size control are difficult, which is not conducive to industrial production. For example, patent CN202410040131.6 discloses a method for preparing nano metal oxide materials by chemical precipitation. The preparation conditions of this method are not harsh, but it is necessary to add a variety of reagents for multi-step reactions, with many preparation steps and a long process cycle. For example, patent CN200410077946.4 discloses a method for preparing a layered composite metal oxide supercapacitor electrode material, which uses a fully back-mixed liquid membrane reactor to carry out a coprecipitation reaction of a cobalt and aluminum mixed salt solution and an alkaline solution, separates the nucleation process and the crystallization process, and controls the conditions of the two processes of nucleation and growth respectively, and finally undergoes high-temperature calcination. Therefore, although similar chemical precipitation methods are one of the most commonly used methods for industrial production of metal oxides, the production process is cumbersome, produces a large amount of waste liquid, requires high temperature, and the coprecipitation conditions are difficult to control, which seriously pollutes the environment and is costly.
[0004] Compared with the above-mentioned traditional preparation technology, the molten salt method is simple and efficient, and the preparation process does not require water medium, does not produce water pollution, has lower energy consumption, and is environmentally friendly. The molten salt used in the molten salt method can be recycled and reused, which is lower in cost. In the field of nanopowder preparation, the molten salt method can currently be used to prepare metal oxides and ion intercalation type two-dimensional materials. For example, CN107697888A discloses a method for preparing metal oxides or metal composite oxides. The method uses a molten salt method to prepare metal oxides or metal composite oxides. During the preparation process, a dispersion carrier and a template must be added. The preparation process has many steps and is difficult to control. For example, CN106629613A discloses a method for preparing an ion intercalation type two-dimensional material powder. The structure of the ion intercalation type two-dimensional material prepared by the molten salt method is a powder formed by intercalating cations, anions or water molecules in the middle of the plate layer.
[0005] The material prepared by the present invention is a metal oxide nano powder. The metal oxide has a simple composition and a wide range of uses. It can be directly used as a functional material and has great potential in many fields. Therefore, the present invention not only provides a method for efficiently preparing metal oxide nano powders by a molten salt quenching method, but also does not require a dispersant and a template agent in the process, has few steps, a short preparation cycle, is easy to control, and is applicable to a variety of metal oxides. By adjusting the type and amount of salt added to the molten salt, regulating the ratio of the quenching liquid, and regulating the reaction time and temperature, the type, morphology, size, and quality of the metal oxide can be very conveniently controlled. The obtained powder can be directly used as a functional material, which is conducive to industrialization. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing metal oxide nanopowder by molten salt quenching method, which can achieve rapid and efficient preparation. The nanopowder prepared by the method of the present invention has controllable morphology and size, strong versatility, low cost, low energy consumption and excellent performance, and comprises the following steps:
[0007] (1) placing the precursor salt from room temperature into an environment with a set temperature;
[0008] (2) heating the precursor salt to a molten state;
[0009] (3) After the precursor salt in step (2) is completely melted, the metal source salt is added, and the reaction is carried out for a predetermined time at a preset temperature, wherein the preset temperature is not lower than the temperature of the molten state in step (2); the purpose of increasing the temperature in step (3) is to ensure that the molten salt does not decompose, and at the same time the metal salt has sufficient energy (heat energy here) to make the molten salt reaction system react uniformly and fully, thereby ensuring the nucleation and growth in the later stage. The specific temperature can be adjusted according to the type and ratio of the molten salt. After the type and ratio of the molten salt in the reaction system are determined, its decomposition temperature is also determined accordingly. Below the decomposition temperature, compared with the reaction temperature in step (2), the higher the temperature is, the more violent the movement of ions in the reaction system is, the easier it is to nucleate but not to grow, and the more product particles there are and the smaller the grain size.
[0010] (4) taking out the reaction system of step (3) and placing it in a liquid for quenching; quenching can make the grain size of the product more uniform and fine, and the morphology and size of the product can be regulated by adjusting the reaction temperature and time. The growth of nanoparticles conforms to the theoretical law of crystal growth. The higher the temperature and the longer the time, the more complete the nucleation and growth, the easier it is to form a three-dimensional structure with a certain orientation, and the larger the size;
[0011] (5) cooling the product of step (4) to room temperature and washing it by centrifugation with deionized water;
[0012] (6) Completely drying the washed product to obtain a metal oxide nanopowder material.
[0013] Preferably, the precursor salt refers to a salt having a melting point below 800° C., including any one or more combinations of the following: nitrate, chloride, sulfate, phosphate, acetate, carbonate.
[0014] Preferably, the metal source salt is a nitrate, sulfate, chloride, phosphate, titanate, tungstate, acetate, molybdate or carbonate of any one of the metal elements copper, manganese, nickel, cobalt, zinc, iron, titanium, aluminum, tin, vanadium, chromium, molybdenum, ruthenium, tungsten, zirconium, lanthanum and cerium.
[0015] Preferably, in the step (4), the liquid used for quenching is deionized water or ethanol aqueous solution; the ethanol mass concentration of the ethanol aqueous solution is lower than 10%; the morphology of the metal oxide nanopowder is regulated by regulating the ethanol mass concentration of the ethanol aqueous solution: within the range of ethanol mass concentration lower than 10%, increasing the ethanol mass concentration makes the morphology of the metal oxide nanopowder form a spherical structure, and reducing the ethanol mass concentration makes the morphology of the metal oxide nanopowder form a polyhedral structure.
[0016] Preferably, the set temperature in step (1) and the temperature of the heat preservation and heating in step (2) are the same, both of which are the melting point of the precursor salt.
[0017] Preferably, in step (3), the preset temperature ranges from the melting point of the precursor salt to a second temperature, the second temperature being the lower value between the decomposition temperature and the boiling point of the precursor salt, and the predetermined time ranges from 3 seconds to 3600 seconds;
[0018] The particle number and grain size of the metal oxide nanopowder in step (6) are regulated by regulating the second temperature: compared with the reaction temperature of step (2), the higher the second temperature, the more violent the movement of ions in the reaction system, the easier it is to nucleate but not to grow, and the more metal oxide nanopowder particles there are and the smaller the grain size.
[0019] Preferably, in step (1), the mass ratio of the precursor salt to the metal source salt is 100 to 0.5:1; within the above range, the ratio of the precursor salt to the metal source salt is regulated to adjust the physical phase and particle size of the metal oxide nanopowder in step (6): the higher the mass ratio of the reactants, the larger the size of the metal oxide nanopowder.
[0020] The main advantages of the present invention are as follows:
[0021] (1) The present invention realizes rapid and efficient preparation of a variety of metal oxide nanopowder materials and is easy for large-scale production;
[0022] (2) By adjusting the ratio of the precursor salt to the metal source salt, the ratio of the quenching liquid, and the reaction temperature and time, the type, morphology, and size of the nanopowder can be regulated. Specifically, by adjusting the ratio of the precursor salt to the metal source salt, the physical phase and product size of the product can be adjusted. The higher the quality of the reactants, the larger the product size; by adjusting the reaction temperature and time, the morphology and size of the product can be regulated. The growth of nanoparticles conforms to the theoretical law of crystal growth. The higher the temperature and the longer the time, the more complete the nucleation and growth, the easier it is to form a three-dimensional structure with a certain orientation, and the larger the size; within the scope of the present invention, the higher the ethanol content in the quenching liquid, the smaller the grain size and the greater the number of particles;
[0023] (3) The present invention utilizes the characteristics of enhanced fluidity when salt is molten, and the high viscosity and polarity of ions in the molten salt quickly form a good match, so that high concentrations of precursor salts and metal source salts can be used, so that the reaction can be carried out efficiently, and a large amount of uniform pure phase nanopowders can be synthesized, which can be directly used as functional materials such as electrodes and catalysts;
[0024] (4) Compared with wet chemical synthesis, the complex ions in the molten salt medium have a smaller Stokes radius than hydrated ions, a lower reaction barrier, and a faster reaction rate.
[0025] (5) The preparation method of the present invention is simple, the preparation process is efficient, rapid, environmentally friendly, low-cost, and the morphology and size of the nanopowder are controllable. The prepared nanopowder is expected to be widely used in electrode materials, catalyst or adsorbent carriers, magnetic materials, desulfurization and denitrification and other energy and environmental fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Some specific embodiments of the present invention will be described in detail in an exemplary but not restrictive manner with reference to the drawings. The same reference numerals in the drawings indicate the same or similar components or parts. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings:
[0027] Figure 1 This is a field emission scanning electron microscope photograph of the CuO nanocones prepared in Example 1.
[0028] Figure 2 This is a field emission scanning electron microscope photograph of the Fe2O3 nanodisk prepared in Example 2.
[0029] Figure 3 This is a field emission scanning electron microscope photograph of the MnO2 nanoflowers prepared in Example 3.
[0030] Figure 4 This is a field emission scanning electron microscope photograph of the NiO nanospheres prepared in Example 4.
[0031] Figure 5 This is the cyclic voltammetry curve of the MnO2 nanosheets prepared in Example 5 as the positive electrode of the zinc ion supercapacitor.
[0032] Figure 6 X-ray diffraction patterns of the metal oxide nanopowders prepared in Examples 6 to 12, specifically: a is TiO2 prepared in Example 6, b is Co3O4 prepared in Example 7, c is ZnO prepared in Example 8, d is SnO2 prepared in Example 9, e is Fe2O3 prepared in Example 10, f is MnO2 prepared in Example 11, and g is MnO2 prepared in Example 12. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0034] Example 1
[0035] (1) Move 10g of sodium nitrate from room temperature to a constant temperature environment of 350℃; (2) Heat the sodium nitrate at 350℃ to make it completely melt; (3) After the sodium nitrate is completely melted, add 0.1g of copper sulfate, maintain the system temperature unchanged, and react for 1 minute; (4) Take out the reaction system of step (3) and quench it in deionized water; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Completely dry the washed product to obtain CuO nanocone material. The field emission scanning electron microscope photo of the obtained nanopowder material is shown in the figure. Figure 1 As shown, the surface morphology observation results show that the nanopowder has an octahedral pyramidal structure with a particle size of about 20 nm in length, and about 10 nm in width and thickness.
[0036] Example 2
[0037] (1) After uniformly mixing 0.4g potassium nitrate and 0.1g potassium chloride, move from room temperature to a constant temperature environment of 380°C; (2) Heat the mixed precursor salt of potassium nitrate and potassium chloride at 380°C to make it completely melt; (3) After the precursor salt is completely melted, add 1g ferric chloride, maintain the system temperature unchanged, and react for 3 seconds; (4) Take out the reaction system of step (3) and place it in a 10% ethanol aqueous solution for quenching; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Completely dry the washed product to obtain Fe2O3 nanodisk material. The field emission scanning electron microscope photo of the obtained nanopowder material is shown in the figure. Figure 2 As shown, the surface morphology observation results show that the nanopowder is a hexagonal disk structure, the nanodisk is formed by multi-layer nanosheet stacking, the diameter of the nanodisk is about 40nm, and the thickness is about 3nm.
[0038] Example 3
[0039] (1) Move 5g of potassium nitrate from room temperature to a constant temperature environment of 380°C; (2) Heat potassium nitrate at 380°C to completely melt it; (3) After the precursor salt is completely melted, add 1g of manganese nitrate, increase the temperature of the reaction system by 20°C to 400°C, and react for 60 seconds; (4) Take out the reaction system of step (3) and quench it in a 5% ethanol aqueous solution; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Completely dry the washed product to obtain a MnO2 nanoflower material. The field emission scanning electron microscope photo of the obtained nanopowder material is shown in the figure. Figure 3 As shown, the surface morphology observation results show that the nanopowder is a spherical nanoflower structure, the surface of the nanoflower is a fine flaky structure, the nanoflower is plush, the diameter of the nanoflower is about 10 to 50 nm, and the thickness of the fine flaky structure on the surface is about 0.5 nm.
[0040] Example 4
[0041] (1) After evenly mixing 5g potassium chloride and 1g sodium chloride, move from room temperature to a constant temperature environment of 800°C; (2) Heat the mixed precursor salt of potassium chloride and sodium chloride at 800°C to make it completely melt; (3) After the precursor salt is completely melted, add 1g nickel nitrate, maintain the system temperature unchanged, and react for 60 seconds; (4) Take out the reaction system of step (3) and quench it in deionized water; (5) Cool the product of step (4) to room temperature and wash it by centrifugation with 10% ethanol aqueous solution; (6) Completely dry the washed product to obtain NiO nanosphere material. The field emission scanning electron microscope photo of the obtained nanopowder material is shown in the figure. Figure 4 As shown, the surface morphology observation results show that the nanopowder has a spherical structure, the nanospheres have good dispersion, and the diameter of the nanospheres is about 10nm.
[0042] Example 5
[0043] (1) Move 5g of potassium nitrate from room temperature to a constant temperature environment of 380℃; (2) Heat potassium nitrate at 380℃ to make it completely melt; (3) After the precursor salt is completely melted, add 1g of manganese nitrate, maintain the system temperature unchanged, and react for 60 seconds; (4) Take out the reaction system of step (3) and place it in a 5% ethanol aqueous solution for quenching; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Dry the washed product completely to obtain MnO2 nanosheet material. The obtained MnO2 nanosheet active material, Ketjen black and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1, and stirred for 2 hours using a magnetic stirrer to make the slurry uniform. The obtained slurry is evenly coated on a 1cm×1cm square area at one end of a 1cm×2cm carbon cloth, and placed horizontally in an oven for drying to obtain a test electrode. Its cyclic voltammetry curve is shown as follows Figure 5 As shown in the figure, the electrochemical performance results show that in 2M zinc sulfate electrolyte, at 2mV s -1 The voltage was scanned at a rate of 1.5 % and the area specific capacitance was calculated to be 925.455 mF cm based on the cyclic voltammetry curve. -2 , indicating that the MnO2 nanosheets prepared by this method have excellent electrochemical properties and good application prospects in electrochemical energy storage.
[0044] Example 6
[0045] (1) Move 0.5g potassium nitrate and 0.5g sodium nitrate mixed precursor salt from room temperature to a constant temperature environment of 280°C; (2) Heat potassium nitrate at 280°C to completely melt it; (3) After the precursor salt is completely melted, add 1g titanyl sulfate, increase the reaction temperature to 500°C, and react for 60 seconds; (4) Take out the reaction system of step (3) and quench it in deionized water; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Dry the washed product completely. The X-ray diffraction spectrum of the obtained nanopowder material is as follows: Figure 6 As shown in curve a, the results show that the oxide is titanium dioxide.
[0046] Example 7
[0047] (1) Move 5g of potassium nitrate from room temperature to a constant temperature environment of 380°C; (2) Heat potassium nitrate at 380°C to completely melt it; (3) After the precursor salt is completely melted, add 0.2g of cobalt chloride, raise the reaction temperature to 400°C, and react for 60 seconds; (4) Take out the reaction system of step (3) and quench it in deionized water; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Dry the washed product completely. The X-ray diffraction pattern of the obtained nanopowder material is as follows: Figure 6 As shown in curve b, the results show that the oxide is cobalt tetroxide.
[0048] Example 8
[0049] (1) Move a mixed precursor salt of 0.5g potassium nitrate and 5g sodium chloride from room temperature to a constant temperature environment of 450°C; (2) Heat the precursor salt at 450°C to completely melt it; (3) After the precursor salt is completely melted, add 1g zinc sulfate, raise the reaction temperature to 600°C, and react for 600 seconds; (4) Take out the reaction system of step (3) and quench it in deionized water; (5) Cool the product of step (4) to room temperature and wash it by centrifugation with deionized water; (6) Dry the washed product completely. The X-ray diffraction spectrum of the obtained nanopowder material is as follows: Figure 6 As shown in curve c, the results show that the oxide is zinc oxide.
[0050] Example 9
[0051] (1) Move a mixed precursor salt of 10g potassium nitrate and 10g sodium nitrate from room temperature to a constant temperature environment of 250°C; (2) Heat the precursor salt at 250°C to make it completely melt; (3) After the precursor salt is completely melted, add 1g tin chloride, maintain the system temperature unchanged, and react for 30 seconds; (4) Take out the reaction system of step (3) and place it in deionized water for quenching; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Dry the washed product completely. The X-ray diffraction spectrum of the obtained nanopowder material is as follows: Figure 6 As shown in curve d, the results show that the oxide is tin oxide.
[0052] Example 10
[0053] (1) Move 10g of potassium nitrate from room temperature to a constant temperature environment of 380°C; (2) Heat potassium nitrate at 380°C to completely melt it; (3) After the precursor salt is completely melted, add 2g of ferric chloride, maintain the system temperature unchanged, and react for 1800 seconds; (4) Take out the reaction system of step (3) and place it in a 5% ethanol aqueous solution for quenching; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Completely dry the washed product. The X-ray diffraction spectrum of the obtained nanopowder material is as follows: Figure 6 As shown in curve e, the results show that the oxide is ferric oxide.
[0054] Embodiment 11
[0055] (1) Move a mixed precursor salt of 10g sodium nitrate and 3g sodium chloride from room temperature to a constant temperature environment of 350°C; (2) Heat the precursor salt at 350°C to completely melt it; (3) After the precursor salt is completely melted, add 1g manganese chloride, maintain the system temperature unchanged, and react for 180 seconds; (4) Take out the reaction system of step (3) and place it in a 2% ethanol aqueous solution for quenching; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Dry the washed product completely. The X-ray diffraction spectrum of the obtained nanopowder material is as follows: Figure 6 As shown in curve f, the results show that the oxide is manganese dioxide.
[0056] Example 12
[0057] (1) Move 10g of potassium nitrate from room temperature to a constant temperature environment of 380°C; (2) Heat potassium nitrate at 380°C to completely melt it; (3) After the precursor salt is completely melted, add 1g of manganese chloride, maintain the system temperature unchanged, and react for 180 seconds; (4) Take out the reaction system of step (3) and place it in a 2% ethanol aqueous solution for quenching; (5) Cool the product of step (4) to room temperature and wash it with deionized water by centrifugation; (6) Dry the washed product completely. The X-ray diffraction pattern of the obtained nanopowder material is as follows: Figure 6 As shown in curve g, the results show that the oxide is manganese dioxide.
[0058] The X-ray diffraction patterns of the metal oxide nanofilm materials prepared in Examples 6 to 12 of the present invention are: a is TiO2 prepared in Example 6, b is Co3O4 prepared in Example 7, c is ZnO prepared in Example 8, d is SnO2 prepared in Example 9, e is Fe2O3 prepared in Example 10, f is MnO2 prepared in Example 11, and g is MnO2 prepared in Example 12. Figure 6 The curve shows that by adjusting different preparation parameters and raw materials, this technology can prepare a variety of metal oxides; Figure 6 The relative peak intensities of the diffraction peaks of the f and g curves show that the crystallinity and quality of manganese oxide nanopowder can be controlled by adjusting the preparation parameters. When the reaction temperature is high, the product has good crystallinity, the amount of precursor salt in the reaction system is large, and the amount of metal source salt is sufficient, the metal source salt in the reaction system participates in the reaction more fully, and the quality of the product is higher.
[0059] The material prepared by the present invention is a metal oxide nano powder, the raw material cost is low, it is easy to obtain, the product has a wide range of uses, the preparation process is simple and efficient, the equipment and atmosphere requirements are low, and it is easy to control. The obtained product can be directly used as a functional material, and has great potential in many fields; unlike the traditional method which usually requires multiple steps and is often accompanied by a high-temperature sintering process at the end, the synthesis method of the present invention has the characteristics of rapidity and efficiency, and the preparation process has lower energy consumption than the commonly used method, and the production process does not use water as a solvent, does not cause water pollution, and is environmentally friendly. The reaction slurry medium can be recycled and reused by appropriate technology. Therefore, the present invention not only provides a method for quickly preparing metal oxide nano powder, but also is applicable to a variety of metal oxides. By adjusting the type and amount of raw materials, reaction time and temperature, the type, morphology, size and quality of the metal oxide can also be easily controlled. The obtained powder can be directly used as a functional material, which is conducive to industrialization.
[0060] The embodiments and applications described above are all specific implementation methods of the technical solution of the present invention, which are further detailed descriptions of the technical solution of the present invention. However, the design concept of the present invention is not limited thereto. Any simple modification, equivalent change or improvement made thereto based on the technical essence of the present invention should still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing metal oxide nanopowder by molten salt quenching method, characterized in that: The steps include: (1) placing the precursor salt from room temperature into an environment with a set temperature; (2) heating the precursor salt to a molten state; (3) after the precursor salt in step (2) is completely melted, a metal source salt is added, and the reaction is carried out at a preset temperature for a predetermined time, wherein the preset temperature is not lower than the temperature of the molten state in step (2); (4) taking out the reaction system of step (3) and placing it in a liquid for quenching; (5) cooling the product of step (4) to room temperature and washing it by centrifugation with deionized water; (6) Completely drying the washed product to obtain a metal oxide nanopowder material.
2. The method for preparing metal oxide nanopowder by molten salt quenching method according to claim 1, characterized in that: The precursor salt refers to a salt with a melting point below 800° C., including any one or more combinations of the following: nitrate, chloride, sulfate, phosphate, acetate, and carbonate.
3. The method for preparing metal oxide nanopowder by molten salt quenching method according to claim 1, characterized in that: The metal source salt is a nitrate, sulfate, chloride, phosphate, titanate, tungstate, acetate, molybdate or carbonate of any one of the metal elements copper, manganese, nickel, cobalt, zinc, iron, titanium, aluminum, tin, vanadium, chromium, molybdenum, ruthenium, tungsten, zirconium, lanthanum and cerium.
4. The method for preparing metal oxide nanopowder by molten salt quenching method according to any one of claims 1 to 3, characterized in that: In the step (4), the liquid used for quenching is deionized water or ethanol aqueous solution; the ethanol mass concentration of the ethanol aqueous solution is lower than 10%; the morphology of the metal oxide nanopowder is regulated by regulating the ethanol mass concentration of the ethanol aqueous solution: within the range of ethanol mass concentration lower than 10%, the ethanol mass concentration is increased so that the morphology of the metal oxide nanopowder forms a spherical structure, and the ethanol mass concentration is reduced so that the morphology of the metal oxide nanopowder forms a polyhedral structure.
5. The method for preparing metal oxide nanopowder by molten salt quenching method according to claim 4, characterized in that: The set temperature in step (1) is the same as the temperature of the heat preservation and heating in step (2), both of which are the melting point of the precursor salt.
6. The method for preparing metal oxide nanopowder by molten salt quenching method according to claim 4, characterized in that: In the step (3), the preset temperature ranges from the melting point of the precursor salt to a second temperature, the second temperature being the lower value between the decomposition temperature and the boiling point of the precursor salt, and the preset time ranges from 3 seconds to 3600 seconds; The particle number and grain size of the metal oxide nanopowder in step (6) are regulated by regulating the second temperature: compared with the reaction temperature of step (2), the higher the second temperature, the greater the particle number and the smaller the grain size of the metal oxide nanopowder.
7. The method for preparing metal oxide nanopowder by molten salt quenching method according to claim 4, characterized in that: In step (1), the mass ratio of the precursor salt to the metal source salt is 100 to 0.5:1; within the above range, the particle size of the metal oxide nanopowder in step (6) is adjusted by regulating the ratio of the precursor salt to the metal source salt: the higher the mass ratio of the reactants, the larger the size of the metal oxide nanopowder.
Citation Information
Patent Citations
Preparation method of layered cobalt aluminium bihydroxy composite metal oxide electrode material
CN100485836C
Preparation method of ionic intercalation type two-dimensional material
CN106629613A
Method for preparing transition metal oxide electrode materials with various shapes
CN107176620A
Method for preparing metal oxides or metal composite oxides
CN107697888A
Preparation method of novel nano metal oxide with uniform particles
CN118084030A
Cited By
Mixed molten salt method for rapidly preparing short-range ordered iridium oxide for PEM electrolyzed water
CN119977008A
Rapid preparation of short-range ordered iridium oxide by a mixed molten salt method for PEM water electrolysis
CN119977008B